PENERAPAN METODE MENGHAFAL (FUN TEORY) DAN PROBLEMATIKANYA DALAM PEMBELAJARAN AL-QUR’AN HADITS DI MTS NEGERI 1 LANGSA - lestari, irma (Program Studi Pendidikan Agama Islam, 2019)
The method of memorizing (fun theory) is a memorizing activity that is packaged in an exciting way, because memorization is usually done by being alone, sitting for a long time and boring but not with this method, they memorize as easily as smiling, students while laughing, joking without feeling already done deliberately 'ah in large quantities. This study aims to find out (1) How is the concept of the method of memorizing (fun theory) in learning the Qur'an in the Hadith at MTs Negeri 1 Langsa? (2) What are the problems encountered in learning Al-Qur'an Hadith by using the method of memorizing (fun theory)? (3) What are the steps taken in dealing with these problems? In conducting this research researchers used qualitative research with a descriptive approach. Data collection techniques used are observation, interviews and documentation. Whereas in analyzing data, researchers used the results of interviews and documentation in the field.